2014
DOI: 10.1159/000358389
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphisms in Sclerostin, Dickkopfs and Secreted Frizzled-Related Protein Genes and Bone Mineral Density in Postmenopausal Korean Women

Abstract: Background/Aims: The purpose of this study was to investigate the association between single nucleotide polymorphisms (SNPs) in sclerostin (SOST), dickkopf (DKK), secreted frizzled-related protein (sFRP) genes and bone mineral density (BMD) in postmenopausal Korean women. Methods: The SOST, Wnt inhibitory factor 1 (WIF1), sFRP1,sFRP2,sFRP3, sFRP4, sFRP5, DKK1, DKK2 and DKK3 polymorphisms were analyzed in 399 postmenopausal Korean women. Serum levels of bone turnover markers were measured, and BMDs at the lumba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
(75 reference statements)
2
4
0
Order By: Relevance
“… 14 However, Lee et al reported that this site may not be a related factor of BMD. 13 Our research data further support the argument that the allelic variation of the rs851056 locus is related to BMD, suggesting that the rs851056 locus may be a susceptible gene locus for T2DM complicated with abnormal bone mass, which may predict changes in bone metabolism index and BMD.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“… 14 However, Lee et al reported that this site may not be a related factor of BMD. 13 Our research data further support the argument that the allelic variation of the rs851056 locus is related to BMD, suggesting that the rs851056 locus may be a susceptible gene locus for T2DM complicated with abnormal bone mass, which may predict changes in bone metabolism index and BMD.…”
Section: Discussionsupporting
confidence: 83%
“…The rs851056 locus was located at the 5ʹ UTR end of the SOST gene, and the genotypes were CC, CG, and GG, respectively. In the present study, the minor allele frequency (MAF) of rs851056 was 0.356, which was comparable to that of postmenopausal women in Korea (0.38), 13 Australia (0.33), 14 Spain (0.38), 15 and Africa (0.350), 16 but lower than the population of postmenopausal women in Shanghai, China (0.391), 17 and the difference of MAF in different studies may be related to ethnic differences, regions, different detection methods and other factors.…”
Section: Discussionsupporting
confidence: 77%
“…It is known that cervical and vaginal epithelial cells experience a growth period during the peri- and postmenopausal processes in normal females at different ages [21,22]. Vaginal endocrine liquid varies with age: the vagina is moist and smooth during the growth period; the vaginal wall is gradually reduced in size, reduces secretions, and exhibits dryness during perimenopause, and almost no vaginal discharge occurs following menopause [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, especially for secreted frizzled-related proteins, which are circulating secreted proteins, they act systematically and may reduce bone mass [64]. …”
Section: Future Perspectivesmentioning
confidence: 99%